Graphic resources for health information visualization in the context of Covid-19 - Laís Alpi Landim; Maria José Vicentini Jorente (InfoDesign: Brazilian Journal of Information Design, 2022)
Objective: To investigate the panorama of the use of graphic resources for health information in the context of Covid-19 and the role of Information Design contributions, in convergence with Information Science, in this context.